Serum metabolomic profiling in patients with Alzheimer disease and amnestic mild cognitive impairment by GC/MS. (22nd June 2020) - Sun, Congcong; Gao, Meimei; Wang, Feifei; Yun, Yan; Sun, Qianwen; Guo, Ruichen; Yan, Chuanzhu; Sun, Xiulian; Li, Yi
Abstract: The aim of this study was to characterize the serum metabolic profiles of patients with Alzheimer's disease (AD) and amnestic mild cognitive impairment (AMCI) using metabolomics based on gas chromatography–mass spectrometry (GC/MS). Serum samples were collected from patients with AD ( n = 30) and AMCI ( n = 32), and normal healthy controls (NOR, n = 40). Metabolite profiles were performed with GC/MS in conjunction with multivariate statistical analysis, and possible biomarker metabolites were identified. Thirty‐one kinds of endogenous metabolites could be identified simultaneously. Eleven components were chosen as biomarker metabolites between AD and NOR groups, and these metabolites were closely related to seven biological pathways: arginine and proline metabolism, phenylalanine metabolism, β ‐alanine metabolism, primary bile acid synthesis, glutathione metabolism, starch and sucrose metabolism, and steroid hormone biosynthesis. Meanwhile, 10 components were chosen as biomarker metabolites between AMCI and NOR groups and seven biological pathways were closely related: arginine and proline metabolism, phenylalanine metabolism, citrate cycle, alanine, aspartate and glutamate metabolism, taurine and hypotaurine metabolism, starch and sucrose metabolism, and steroid hormone biosynthesis. Our study distinguished serum metabotypes between AD, AMCI and NOR patients successfully. The implementation of this metabolomic strategy may help to develop biochemical insight into the metabolic alterations in AD/AMCI and will be helpful for the further understanding of pathogenesis.